Interior of Analytical Laboratory at Dow Chemical Company - Dow Chemical Company (1988)
Interior view of the Analytical Laboratory at the Dow Chemical Company facilities in Midland, Michigan. Assorted analytical instruments and computational equipment is visible throughout the laboratory, including a Hewlett-Packard computer station. The words "Mass Spec" are stenciled on the wall on the right-hand side.
Keywords: Laboratories; Dow Chemical Company; Scientific apparatus and instruments